KONSEP PEREMPUAN DI MINANGKABAU: Analisa Sosiolinguistik Tentang Konsep Bundo Kanduang - Irwan Irwan (State Institute of Islamic Studies Batusangkar, 2017)
This article discussess about the concept of woman in Minangkabau culture. Untill now people are still in doubt about the meaning of the word of Bundo Kanduang. The meaning of Bundo Kanduang which have been kept into the mind of most people is “a queen” or “a king” who ever had a good position in Pagaruyung kingdom. She was described as a very perfect woman. But in fact, that story was not really true because it was found in some Minangkabau manuscripts that Bundo Kanduang means a concept of woman in Minangkabau, not a real woman which ever occupied a kingdom in 13th century